Penerapan Metode Item-Based Collaborative Filtering pada Sistem Electronic Commerce Berbasis Website (Studi Kasus : Toko Buku Online di Indonesia) - Rio Abdi Sucipta; Pacu Putra; Fathoni Fathoni (Annual Research Seminar (ARS), 2016)
The rapid development of e-commerce lead to changes in the way to transact the sale of goods and services from conventional to digital. Competition between providers of e-commerce services makes consumer-based service approach needs to be improved. One way is to give product recommendations to prospective buyers. Some e-commerce service providers website do not provide product recommendations to prospective buyers in accordance with their preferences causes more time needed to explore each book available. Therefore, the purpose of this research is to build an e-commerce system that can provide product recommendations to prospective purchasers resulting from item-based collaborative filtering algorithm. This research was conducted using the method of development of the V-Model and some tools that help the system design process include DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), and DBMS (Database Management System) MySQL. Results from this study is an e-commerce system that applies the algorithm producing book recommendations. Each member has a different recommendation system in accordance with the rate values previously assigned.